Advances in the research on micropropagules and their role in green tide outbreaks in the Southern Yellow Sea. (March 2023) - Cao, Jiaxing; Liu, Jinlin; Zhao, Shuang; Tong, Yichao; Li, Shuang; Xia, Zhangyi; Hu, Meijuan; Sun, Yuqing; Zhang, Jianheng; He, Peimin
Abstract: The green tide event that occurred in the Southern Yellow Sea in 2007 lasted for 16 years, causing serious economic losses and ecological damage to coastal cities. To address this problem, a series of studies were conducted. However, the contribution of micropropagules to green tide outbreaks remains poorly understood, and the relationship between micropropagules and green algae that are settled nearshore or floating at sea also needs to be further explored. The present study focuses on the identification of these micropropagules in the Southern Yellow Sea and uses the Citespace tool to quantitatively analyze current research hotspots, frontier trends, and development trends. In addition, it examines the micropropagules' life cycle and how it directly affects the green algal biomass and clarifies the temporal and spatial distribution of micropropagules in the entire Southern Yellow Sea. The study also discusses unresolved scientific problems and limitations in the current research on algal micropropagules and provides an outlook on future research directions. We expect to further analyze the contribution of micropropagules to green tide outbreaks and provide data to support comprehensive green tide management. Highlights: A new definition of green algae micropropagules. The green algae micropropagules were studied using a novel method called Citespace. The role of micropropagules in the entire green tide cycle was clarified. The patterns and causes of micropropagules' spatiotemporal distribution were investigated. The micropropagule control methods were summarized.